Adjustments in β-adrenergic signaling contribute to the amelioration of cardiac dysfunction by exercise training in supravalvular aortic stenosis - De Souza, Sérgio Luiz Borges [UNESP] (2020)
Background/Aims: Aortic stenosis-induced chronic pressure overload leads to cardiac dysfunction and congestive heart failure. The pathophysiological mechanisms of the myocardial impairment are multifactorial and include maladaptive β-adrenergic signaling. Exercise training (ET) has been used as a non-pharmacological therapy for heart failure management. The present study tested the hypothesis that exercise training attenuates diastolic dysfunction through β-adrenergic signaling preservation. Methods: Wistar rats were submitted to ascending aortic stenosis (AS) surgery, and after 18 weeks, a moderate aerobic exercise training protocol was performed for ten weeks. Results: ET attenuated diastolic dysfunction, evaluated by echocardiogram and isolated papillary muscle (IPM) assay. Also, ET reduced features of heart failure, cross-sectional cardiomyocyte area, and exercise intolerance, assessed by treadmill exercise testing. The β2 adrenergic receptor protein expression was increased in AS rats independently of exercise. Interestingly, ET restored the protein levels of phosphorylated phospholamban at Serine 16 and preserved the β-adrenergic receptor responsiveness as visualized by the lower myocardial compliance decline and time to 50% tension development and relaxation during β-adrenergic stimulation in the IPM than untrained rats. Additionally, AS rats presented higher levels of TNFα and iNOS, which were attenuated by ET. Conclusion: Moderate ET improves exercise tolerance, reduces heart failure features, and attenuates diastolic dysfunction. In the myocardium, ET decreases the cross-sectional area of the cardiomyocyte and preserves the β-adrenergic responsiveness, which reveals that the adjustments in β-adrenergic signaling contribute to the amelioration of cardiac dysfunction by mild exercise training in aortic stenosis rats.